Determinants of tax compliance behavior among central Java SMEs: The mediating role of intention to comply - Hikmah Hikmah; Andalan Tri Ratnawati; Susetyo Darmanto (Universitas Muhammadiyah Yogyakarta, Indonesia, 2024)
Research aims: This study aims to prove the effect of tax compliance attitude, subjective norms, and perceived financial performance on the intention to comply. Furthermore, the study analyzes the effect of perceived financial performance and intention to comply with tax compliance behavior.Design/Methodology/Approach: This study used a quantitative approach with primary data from distributing questionnaires. The samples collected were 150 SMEs of Semarang City, Semarang Resident, Demak, and Kendal. The data were then analyzed employing Structural Equation Modeling calculated by Amos version 22.Research findings: Empirical findings demonstrated that attitudes toward tax compliance, subjective norms, and perceived financial performance positively influenced the intention to comply. Furthermore, perceived financial performance and intention to comply positively contributed to compliance behavior.Theoretical contribution/ Originality: This theoretical implication integrates the Theory of Planned Behavior and perceived financial performance as an alternative to perceived behavioral control.Practitioner/Policy implication: This study concludes that intention to comply provides a mediating role in the determinants of tax compliance.Research limitation/Implication: This research was limited by the unavailability of accurate data regarding the number of SMEs in Central Java, so sample calculations could not be done using a statistical approach. Future research is recommended to replicate this model in large companies by adding government policy as a moderating role in attitudes, subjective norms, and financial performance.